After Abitur, first an apprenticeship and then university? : Why German Abitur holders are taking vocational training in the financial services sector - Pilz, Matthias [Verfasser] (My University, 2009)
"In the financial services sector in Germany the proportion of trainees qualified to go on to university is particularly high. But what induces school leavers not to go (straight) to university? A written survey of over 500 trainees in the banking and insurance sectors examined the motivations for the choice of educational pathway. Only some of the motivations cited in academic debate were mentioned by the trainees surveyed. For those surveyed who were from the financial sector it was not possible to confirm that trainees qualified to go on to university performed relatively poorly at school. Nor was it possible to discover any particularly marked risk aversion. It was more the case that the persons surveyed saw benefits in doing an apprenticeship to keep all their options open and to achieve a good combination of theory and practice. However, those questioned who had no intention of going on to university chose continuing training primarily because, besides being practice oriented, it offers a fast path to affluence and good career prospects." (Autorenreferat, BIBB-Doku)
Keywords: G 1.3.2.1.2 Hochschulzugangsberechtigung; G 1.2.4.2.4 Kredit und Versicherung; 370; Abitur; Bildungsverhalten; Bildungsverlauf; Doppelqualifikation; Berufsausbildung; Duales System; Bankgewerbe; Quantitative Angaben